Efektifitas Hubungan Kerjasama Green Sister City Kota Surabaya dengan Kitakyushu - Khoirul Ummah; Amirah Hilyatun Nisa; Dyah Estu Kurniawati; Eko Priyo Purnomo (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
This study aims to see the relationship of Sister City cooperation between the city of Surabaya and Kitakyushu in realizing the Green City of Surabaya. The focus of this research is to determine the effectiveness of the relationship between the two countries in realizing the Green City of Surabaya. This study uses an analytical method based on secondary data obtained from books, journals, and news in accordance with the research analyzed by the author. A qualitative approach is used to see the phenomenon of research that focuses on the effectiveness of the relationship between the Sister City of Surabaya and Kitakyushu in realizing the Green City of Surabaya. The results of this study indicate that there are policies and programs of cooperation between the city of Surabaya and Kitakyushu in the Sister City relationship in order to realize a more effective relationship in realizing the Green City of Surabaya. The cooperation between the two cities is known to have existed since 1997 but encountered various obstacles, so that in 2012 a Sister City collaboration was established with various policies and programs that were more effective in realizing the Green City of Surabaya. The collaboration between the two cities focuses on overcoming environmental problems that are often experienced by industrial cities in the world.